ADOPSI E-PRECOREMENT PADA KEGIATAN PENGADAAN BARANG JASA PEMERINTAH INDONESIA: Suatu Telaah TOE Model - Stefanus Ardy Susantya, (2021)
Indonesia is facing on Industrialization 4.0 and the government is willing to use its innovations, so e-government's propaganda realized and e-precorement as its product that applied for the first stage in Indonesia. This study aims to examine the TOE's factors against the Indonesian e-precorement adoption with diffusion of innovation theory to develop its notion. This study used purposive sampling technique that the samples are State-owned enterprises with its subsidiaries and others private enterprises in infrastructure and construction sector who participated in Indonesian e-precorement. This study used primary data and smartPLS version 3.0 as a tool to examine data so the results are top mangement support and information sharing culture has positive and significant effect to eprecorement adoption and perceived cost, firm size, business partner influence has no significant effect to e-precorement adoption presented in this study. This study is still need research to develop in the future especially the review of any enterprise who participated in Indonesian e-precorement.